Determining Customer Satisfaction on Service Quality Constructs Using SERVQUAL Model: Evidence from India’s Rural Banks (Global Journal of Management and Business Research, 2022)
The present research piece aims to determine customers satisfaction with services offered by rural banks in India The study has considered a total of 400 customers who are directly associated with the banks i e at least having one account with the banks using the purposive sampling method The opinion of the respondents on the selected variables indicating satisfaction dissatisfaction level was measured on a Likert scale
Keywords: service quality; correlation matrix; rural bank; SERVQUAL; customer satisfaction